2018
DOI: 10.1021/acsmacrolett.8b00561
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Biocatalysts to Control Radical Polymerizations

Abstract: Reversible-deactivation radical polymerizations (controlled radical polymerizations) have revolutionized and revitalized the field of polymer synthesis. While enzymes and other biologically derived catalysts have long been known to initiate free radical polymerizations, the ability of peroxidases, hemoglobin, laccases, enzyme-mimetics, chlorophylls, heme, red blood cells, bacteria, and other biocatalysts to control or initiate reversible-deactivation radical polymerizations has only been described recently. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 114 publications
0
38
0
Order By: Relevance
“…However, considering the aspect of efficiency and cost of the enzymes, immobilization of the enzymes would be more beneficial in order to recover and recycle the enzymes after the reaction. In addition, the utilization of oxidoreductase in catalyzing controlled radical polymerizations start to gain much attention in recent years . Therefore, future experiments will focus on biocatalytic methods for creating well‐defined glycopolymer structures, which are highly interesting for biomedial applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering the aspect of efficiency and cost of the enzymes, immobilization of the enzymes would be more beneficial in order to recover and recycle the enzymes after the reaction. In addition, the utilization of oxidoreductase in catalyzing controlled radical polymerizations start to gain much attention in recent years . Therefore, future experiments will focus on biocatalytic methods for creating well‐defined glycopolymer structures, which are highly interesting for biomedial applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the utilization of oxidoreductase in catalyzing controlled radical polymerizations start to gain much attention in recent years. [68] Therefore, future experiments will focus on biocatalytic methods for creating well-defined glycopolymer structures, which are highly interesting for biomedial applications.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, toxicity and negative environmental aspects of the required transition metal complex catalysts limit the application of ATRP-derived polymers in the medical sector or in the food industry, and push researchers to look for alternative solutions, such as highly active catalytic systems, non-toxic catalysts, or catalysts obtained from renewable resources. 2,4,7 Since the first reported use by Wallace and coworkers in 1989, enzymes have been used for the production of polymers 8 and have since been established as catalysts to initiate free radical polymerizations. [9][10][11][12][13][14][15] However, the first use of enzymes in RDRP has only been reported in recent years by our group and by di Lena and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] However, the first use of enzymes in RDRP has only been reported in recent years by our group and by di Lena and coworkers. 7,[16][17][18] We found that horseradish peroxidase (HRP) catalyzed the polymerization of N-isopropylacrylamide (NIPAAm) under activator regenerated by electron transfer (ARGET) ATRP conditions 16 whereas di Lena and coworkers showed that laccase and catalase could initiate polymerizations of poly(ethylene glycol) methyl ether methacrylate (PEGMA). 17,18 Since then, our group and others have demonstrated that metal-containing enzymes such as HRP, [19][20][21][22] laccase, 19,23 hemoglobin, [24][25][26][27] and catalase 19,28 can act as ATRP catalysts with distinct advantages, such as the ability to control the polymerizations of difficult monomers, which traditional ATRP conditions fail, 23 to confine polymerizations into nanoreactors, 20,21 to prepare biosensors, 26,27 and to tune surface-initiated polymerizations by the protein affinity of surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation